Berberine inhibits NLRP3 Inflammasome pathway in human triple-negative breast cancer MDA-MB-231 cell - Yao, Mingjiang (BMC Complement Altern Med, 2019)
BACKGROUND: Breast cancer is still the most common malignant tumor that threatens the female’s life in the world, especially triple-negative breast cancer (TNBC), one of the most difficult subtypes. Lack of targeted therapies brings about urgent demand for novel treatments. In this study we aim to investigate the anti-tumor activity of Berberine (BBR), a Chinese plant-derived alkaloid, against the TNBC cell line MDA-MB-231 and elucidate its mechanism referring to anti-inflammation. METHODS: Cell inhibition rate was measured by Cell Proliferation Assay, the cytotoxic effects was detected by Lactate dehydrogenase (LDH) leakage assay, the colony formation and migration potential were evaluated by colony formation assay and wound healing assay, the release of inflammatory cytokines was detected by EMD multifactor detection, and alterations of proteins and genes related to the NLR family pyrin domain containing 3 (NLRP3) inflammasome pathway were analyzed using western blotting and real-time Polymerase Chain Reaction (PCR). RESULTS: BBR reduce the viability of MDA-MB-231 cells and increased the release of LDH from the cells in a dose-dependent manner, with and inhibition of colony formation potential and migration of the cells. BBR also caused a marked reduction in the secretion of proinflammatory cytokines, Interleukin-1α (IL-1α), Interleukin-1β (IL-1β), Interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α). Besides, a down-regulated behavior was observed with the expression of P2X purinoceptor 7 (P2X7), NLRP3, pro-caspase-1, apoptosis-associated speck-like protein containing a caspase-activation and recruitment domain (ASC), caspase-1 p20, Interleukin-18 (IL-18), IL-1β proteins and NLRP3, Caspase-1 and ASC mRNAs in the NLRP3 inflammasome cascade. CONCLUSIONS: Our results confirmed that BBR can effectively affect both tumor outgrowth and spontaneous metastasis in TNBC, and that we identified a new mechanism associated with inhibition the NLRP3 inflammasome pathway, suggesting its potential therapeutic relevance in clinical use.